Association of Nitrate, Nitrite, and Total Organic Carbon (TOC) in Drinking Water and Gastrointestinal Disease. (15th April 2013) - Khademikia, Samaneh; Rafiee, Zahra; Amin, Mohammad Mehdi; Poursafa, Parinaz; Mansourian, Marjan; Modaberi, Amir
Abstract : Objective . We aimed to investigate the amounts of nitrate, nitrite, and total organic carbon (TOC) in two drinking water sources and their relationship with some gastrointestinal diseases. Methods . This cross-sectional study was conducted in 2012 in Iran. Two wells located in residential areas were selected for sampling and measuring the TOC, nitrate (NO3 − ), and nitrite (NO2 − ). This water is used for drinking as well as for industrial and agricultural consumption. Nitrate and nitrite concentrations of water samples were analyzed using DR 5000 spectrophotometer. The information of patients was collected from the records of the main referral hospital of the region for gastrointestinal diseases. Results . In both areas under study, the mean water nitrate and nitrite concentrations were higher in July than in other months. The mean TOC concentrations in areas 1 and 2 were 2.29 ± 0.012 and 2.03 ± 0.309, respectively. Pollutant concentration and gastrointestinal disease did not show any significant relationship ( P > 0.05 ) . Conclusion . Although we did not document significant association of nitrite, nitrate, and TOC content of water with gastrointestinal diseases, it should be considered that such health hazards may develop over time, and the quality of water content should be controlled to prevent different diseases.